Financial Ratio Determinants of Capital in the Banking Sector Listed on the Indonesia Stock Exchange (IDX) - Putra, Revian Nico Pradana; Asyik, Nur Fadjrih; Fidiana, . (Archives of Business Research, 2020)
This research raises the topic "Financial Determinants of Capital in the Banking Sector Listed on the Indonesia Stock Exchange (BEI)". The population in this study are conventional banking companies listed on the Indonesia Stock Exchange (BEI). The sample in this study were 26 conventional banking companies listed on the Indonesia Stock Exchange that published annual reports from 2014 to 2018. The sampling technique used in this research was purposive sampling method. Analysis of the data in this study using Multiple Linear Regression Analysis, while testing the hypothesis using the F test, R2, and t test. From the results of the F test, the significance value is 0.002. The significance value is less than 0.05. So it can be concluded that the variable Return on Assets (ROA), Operational Costs on Operational Income (BOPO), Non Performing Loans (NPL) and Loan to Deposit (LDR) have a regression equation that is a fit model. The value of R Square is 0.998 or 99.8%, which means that the ability of the independent variables ROA, BOPO, NPL and LDR to explain the dependent variable CAR is 99.8%. The correlation value (R) of 0.397 or 39.7% indicates the correlation or closeness of the relationship between the independent variables, namely ROA, BOPO, NPL and LDR to the dependent variable, namely CAR, is 39.7%. In the ROA variable, it has a t value of 164,987 and a significance value of 0.023 which is smaller than 0.05, it can be concluded that ROA has an effect on CAR. The BOPO variable has a t value of 0.330 and a significance value of 0.743 which is greater than 0.05, it can be concluded that BOPO has no significant effect on CAR. In the NPL variable, it has a t value of -0.515 and a significance value of 0.608 which is greater than 0.05, it can be concluded that NPL has no effect on CAR distribution. In the LDR variable, it has a t value of 1,224 and a significance value of 0.225 greater than 0.05, it can be concluded that the LDR has no significant effect on CAR.